Cyprus and Sardinia in the Late Bronze Age: Nuragic table ware at Hala Sultan Tekke. (October 2020) - Gradoli, Maria G.; Waiman-Barak, Paula; Bürge, Teresa; Dunseth, Zachary C.; Sterba, Johannes H.; Schiavo, Fulvia Lo; Perra, Mauro; Sabatini, Serena; Fischer, Peter M.
Highlights: Table ware from 13th c. BC at Hala Sultan Tekke, Cyprus, was identified as Sardinian. Cypriot and Sardinian ceramics and sediments were analysed by petrography. Additional analyses include NAA and FTIR. Results confirm trade related connections between Hala Sultan Tekke and Sardinia. Abstract: In the course of the Swedish excavations at Hala Sultan Tekke, Cyprus, table ware and domestic pottery of unknown provenance were discovered in offering pits dating to the 13th century BCE. These vessels comprise six hand-made and black burnished vessels, all of which have close typological parallels in the Nuragic culture of Sardinia. Comparative petrographic investigation confirmed their Sardinian provenance. Other archaeometric analyses include FTIR on the Cypriot and Sardinian material, and NAA on the Sardinian vessels from Hala Sultan Tekke. These vessels further extend the nature of intercultural relations of the site, which comprise a vast area including the Aegean, Anatolia, the Levant and Egypt. The paper presents the archaeometric results and briefly discusses their implication for Cypro-Sardinian connections in the Late Bronze Age.